PENGEMBANGAN ALGORITMA PEMBUATAN TASK ASSIGNMENT PADA FINAL ASSEMBLY LINE PESAWAT NC-212i PT DIRGANTARA INDONESIA - Daniel Lt, Victor
PT Dirgantara Indonesia is the only company in Indonesia which is engaged in aeronautics. In addition to producing aircraft, the company also produces helicopters and aircraft guns. One of the company's most ordered aircrafts is the NC-212i. The demand for NC-212i in a year is six units. However, company can only produce four units NC-212i in a year for now. The aircraft manufacturing process is divided into four stages, they are detailed part manufacturing, surface treatment, component sub-assembly, and final assembly. The NC-212i's final assembly process currently lasts for around three to four months. To be able to meet the demand for 6 units a year, the NC-212i's final assembly process must be completed within 18525 minutes or around 41 working days. The current production plan schedules the final assembly activity with a cycle time of 18419 minutes and require 288 manpowers. But the cycle time cannot be achieved because there is no clear task assignment for each technician. This resulted in the NC-212i's final assembly line lacking technician when needed and the work did not go according to the schedule that was made. The problem owner desire an algorithm that can create task assignments and can reduce the amount of manpower needed. The model used in this study schedules task based on Critical Path & Longest Processing Time priorities and assigns them to a number of manpower to achieve the desired cycle time. The procedures for determining the critical path, sorting, scheduling, and assigning task are performed with the VBA / MACRO programming algorithm in Microsoft Excel. Computing produces a schedule and division of work elements with a cycle time of 18419 minutes and require 148 manpowers.